Integration of Islamic Values and Local Wisdom of the Orang Rimba in Archipelago Character Education - Sudrajat, Ajat (Proceedings: International Seminar On Educational Studies, 2025)
This research is motivated by the moral and identity crisis in national education, which tends to emphasize cognitive aspects and neglect spiritual and local cultural dimensions. In fact, the traditions of the archipelago contain noble values that are in harmony with Islamic teachings, as seen in the indigenous Orang Rimba community in Jambi, which has a natural education system based on life experiences. This study aims to analyze the Islamic values and local wisdom of the Orang Rimba, identify their compatibility within the framework of Tamadun Islam Nusantara, and develop a conceptual model of character education based on the integration of Islamic values and local wisdom. The approach used is descriptive qualitative with an interpretive paradigm through literature study, document analysis, indirect observation, and source triangulation. The results show that there is synchronization between Islamic values and local culture in five main dimensions—spiritual, social, ecological, moral, and intellectual—which reflect the principles of tauhid, ukhuwah, khilafah fil ardh, ta'dib, and iqra', respectively. The integration of these values forms a contextual character education model that strengthens the Islamic civilization of the Archipelago as an educational paradigm that is down-to-earth, inclusive, and civilized. The novelty of this research lies in the formulation of a character education model based on Islamic values and local wisdom that is relevant to the Merdeka Belajar (Freedom of Learning) policy. The implications of this research emphasize the importance of developing a curriculum based on local culture and further research on Islamic ethnopedagogy to strengthen national character education.